2019
DOI: 10.3390/antiox8120644
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Unsaponifiable Matter from Perilla Seed Meal on UVB-induced Damages and the Underlying Mechanisms in Human Skin Fibroblasts

Abstract: Unsaponifiable matter (USM) from perilla seed meal contains numerous phytochemicals, including tocopherols, phytosterols, squalene, and policosanols, that exhibit antioxidant and health-promoting properties. In this study, the protective effects of USM on UVB-induced skin aging were investigated in Hs68 cells. UVB irradiation decreased cell viability by 26% compared to the control. However, USM blocked UVB-induced cytotoxicity. Moreover, USM treatment significantly decreased the UVB-induced production of react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…The protective effects of UVB-induced damages were also examined using unsaponifiable matter (USM) from perilla seed meal [23]. Similar results detected in the present study were observed in USM-treated human skin fibroblasts (Hs68 cells) after UVB radiation although there are differences in the analysis factors.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The protective effects of UVB-induced damages were also examined using unsaponifiable matter (USM) from perilla seed meal [23]. Similar results detected in the present study were observed in USM-treated human skin fibroblasts (Hs68 cells) after UVB radiation although there are differences in the analysis factors.…”
Section: Discussionsupporting
confidence: 84%
“…Similar results detected in the present study were observed in USM-treated human skin fibroblasts (Hs68 cells) after UVB radiation although there are differences in the analysis factors. USM treatment at 1.0, 2.5 and 5.0 µg/mL suppressed UVB-induced cytotoxicity and ROS production in Hs68 cells [23]. Furthermore, decrease of total collagen production in UVB treated cells significantly recovered by USM treatment, while the opposite pattern observed on MMP1 and 3 secretion and mRNA under the same condition [23].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Reactive oxygen species (ROS) play an important role in human health because they are related to various diseases. Abnormal ROS production leads to various adverse effects, including damage to essential macromolecules such as DNA, lipids, and proteins [ 30 , 31 , 32 , 33 , 34 ]. Accumulation of this molecular damage can subsequently cause cell apoptosis, necrosis, and death.…”
Section: Resultsmentioning
confidence: 99%